Neuropsychiatric and Neurocognitive Manifestations in HIV-Infected Children Treated With Efavirenz in South Africa—A Retrospective Case Series - Hammond, Charles K.; Eley, Brian; Ing, Natalia; Wilmshurst, Jo M. (Frontiers in Neurology, 2019)
Background: Efavirenz is associated with transient neuropsychiatric manifestations but the impact on neurocognition in children is unknown. Genetically slow metabolizers of efavirenz may be at risk of toxicity. This study describes neuropsychiatric and neurocognitive manifestations of South African children with suspected efavirenz neurotoxicity. Method: This retrospective study describes clinical features of 12 children with features consistent with efavirenz neurotoxicity between 2008 and 2014. Results: Twelve children (4 males, 8 females) aged 3–12 years (median 8.4 years) were referred to a dedicated pediatric neuroHIV service. Eight were of indigenous African (black) ancestry and 4 were of mixed ancestry. The total duration on efavirenz-containing ART at the time of referral was 6–72 (mean 31) months. Two children (both of black ancestry) were phenotypically slow metabolizers and presented with acute manifestations and high plasma efavirenz concentrations above normal range resulting in discontinuation of efavirenz. Ten other children had clinical presentations compatible with efavirenz neurotoxicity but had normal or sub-therapeutic plasma efavirenz concentrations and continued treatment with efavirenz. The acute neuropsychiatric manifestations reported included drowsiness, seizures, sleep disturbances, personality changes, ataxia, and slurred speech. These were noticed 2–8 weeks (mean 5 weeks) after commencing efavirenz and resolved over a few weeks. Nine children had neurocognitive deficits and showed poor performance in all neurocognitive domains that were tested. Interpretation: Efavirenz causes transient neuropsychiatric adverse effects and may contribute to poor long-term neurocognitive outcomes in HIV-infected children. Prospective studies comparing efavirenz-treated and efavirenz-naïve children are needed to further elucidate the manifestations of efavirenz toxicity.